Signals from damaged but not undamaged skeletal muscle induce myogenic differentiation of rat bone-marrow-derived mesenchymal stem cells - Santa María, Lorena; Rojas, Cecilia V.; Minguell, José J. (Experimental cell research, 2004)
The regenerative capacity of skeletal muscle has been usually attributed to resident satellite cells, which, upon activation by local or distant stimuli, initiate a myogenic differentiation program. Although recent studies have revealed that bone-marrow-derived progenitor cells may also participate in regenerative myogenesis, the signals and mechanisms involved in this process have not been elucidated. This study was designed to investigate whether signals from injured rat skeletal muscle were competent to induce a program of myogenic differentiation in expanded cultures of rat bone-marrow-derived mesenchymal stem cells (MSC). We observed that the incubation of MSC with a conditioned medium prepared from chemically damaged but not undamaged muscle resulted in a time-dependent change from fibroblast-like into elongated multinucleated cells, a transient increase in the number of MyoD positive cells, and the subsequent onset of myogenin, α-actinin, and myosin heavy chain expression. These results show that damaged rat skeletal muscle is endowed with the capacity to induce myogenic differentiation of bone-marrow-derived mesenchymal progenitors.